The Difficulites for European Identity: Discourse, Culture, Politics and Post-nationalism - Švarplys, Andrius (Sociologija. Mintis ir veiksmas, 2008)
The paper expresses constructivist approach to the issue, asking the question: what there are essiantialdiscourses on European identity problem? The cultural, national, philosophical and political discourses shape European identity.The analysis of each of them shows that the efforts to universalise common European culture in the cultural-political discourse result in European Union as transnational state with actually the samefeatures as of a national state only on the higher supra-national level. The final result is either unfavourable Euronationalism and Eurocentrism, or everlasting confrontation between national and euro identity. The alternative way is to cunstruct postnational identity, which means that European identity definition should contain any cultural references (because all cultural meanings still remain national). Postnational European identity receives constitutional face, because people recognize constitutional values as universal while still owning national identities.
Keywords: European Identity; National Identity; Cultural Identity; Discourse; European Union; Postnational